Rosa Luxemburg Band 2: Nachwirken - Jacob, Frank; Scharenberg, Albert; Schütrumpf, Jörn (Büchner-Verlag, 2021)
The year 2021 marks the 150th anniversary of Rosa Luxemburg's birth. Even though she met a violent death in the course of the 1918/19 revolution and much has subsequently been done to diminish her memory, her works remain an inspiration to this day for all those who seek to create a new, better, and more just world. This volume brings together works by German-speaking and international scholars who address Luxembourg's aftermath from different perspectives and with different questions. In their entirety, they underscore the important significance that Luxemburg's thoughts still have today.